Comparative Analysis of SMK Students' Understanding of Electrochemistry Through Laboratory-Based and Virtual Laboratory-Based Learning Modalities - Alvin Annayya Habibah; Hartinah Pratiwi; Kurnia Larasati; Anugrah Ricky Wijaya (J-PEK (Jurnal Pembelajaran Kimia), 2025)
This study investigates the comparative effectiveness of Lab-Based Learning (LBL) and Virtual Lab-Based Learning (VLL) models in enhancing electrochemistry comprehension among Vocational High School (SMK) students. Employing a quasi-experimental, pre-test-post-test non-equivalent control group design, the research involved two groups of Industrial Chemistry students, each subjected to either LBL or VLL instructional methods. Data collection instruments included a concept understanding test and a student perception questionnaire. Initial assessments indicated similar baseline understanding, with pretest mean scores of 39.00 across all participants. Post-intervention results demonstrated significant improvements in both groups: the VLL group's mean score increased from 39.67 to 80.47, while the LBL group's mean rose from 38.33 to 88.67. Statistical analysis confirmed that both models effectively enhanced students' electrochemistry understanding, with the LBL group exhibiting a greater mean increase. Student perceptions further revealed a preference for the LBL model, citing increased engagement and ease of comprehension. These findings suggest that, despite the advantages of virtual laboratories, authentic laboratory experiences remain more effective for vocational students in mastering complex electrochemical concepts.